2022
DOI: 10.1186/s12920-022-01212-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of potential genetic biomarkers using machine learning methods and immune infiltration regulatory mechanisms underlying atrial fibrillation

Abstract: Objective We aimed to screen out biomarkers for atrial fibrillation (AF) based on machine learning methods and evaluate the degree of immune infiltration in AF patients in detail. Methods Two datasets (GSE41177 and GSE79768) related to AF were downloaded from Gene expression omnibus (GEO) database and merged for further analysis. Differentially expressed genes (DEGs) were screened out using “limma” package in R software. Candidate biomarkers for AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 72 publications
(62 reference statements)
1
11
0
Order By: Relevance
“…And atrial electrophysiology and structural substrates can be altered by mediators of the inflammatory response, thus increasing the risk of atrial fibrillation [29]. Furthermore, several clinical studies have demonstrated increased infiltration of proinflammatory immune cells in the atrial myocardium of AF patients [30]. Bhat et al demonstrated that the neutrophil-to-lymphocyte (NLR) ratio was an independent predictor of outcomes in patients with stable coronary artery disease and an independent predictor of prognosis in patients with acute coronary syndromes [31].…”
Section: Discussionmentioning
confidence: 99%
“…And atrial electrophysiology and structural substrates can be altered by mediators of the inflammatory response, thus increasing the risk of atrial fibrillation [29]. Furthermore, several clinical studies have demonstrated increased infiltration of proinflammatory immune cells in the atrial myocardium of AF patients [30]. Bhat et al demonstrated that the neutrophil-to-lymphocyte (NLR) ratio was an independent predictor of outcomes in patients with stable coronary artery disease and an independent predictor of prognosis in patients with acute coronary syndromes [31].…”
Section: Discussionmentioning
confidence: 99%
“…40 An example of this is quantifying biomarkers for disease states in tissues. [41][42][43] In the aforementioned diagnostics context, each of the masked pixels taken from the 4 × 4 MM is treated as an instance in our dataset. Each instance has 16 features, with each feature corresponding to one of the 16 channels of the MM.…”
Section: Artificial Intelligence and Machine Learning Techniquesmentioning
confidence: 99%
“…Another common task is regression, in which the model typically predicts continuous, numerical values instead of discrete labels 40 . An example of this is quantifying biomarkers for disease states in tissues 41 43 …”
Section: Background and Related Workmentioning
confidence: 99%
“…Medicine is one of the earliest applications of AI, including disease diagnosis and the selection of the best surgical procedures ( Goyal et al, 2022 ). Machine learning is an important branch of artificial intelligence and has been widely used in screening characteristic genes and risk factors of diseases ( Dai et al, 2022 ; Liu et al, 2022 ; Wu et al, 2022 ). We also used machine learning methods to screen characteristic genes in subgroups in an attempt to correlate gene expression profiles with clinical features in patients with DCM.…”
Section: Introductionmentioning
confidence: 99%